Mapping of the HIDRA stellarator magnetic flux surfaces - Rizkallah, Rabel; Marcinko, Steven; Curreli, Davide; Parsons, Matthew S.; Bartlett, Nathan; Gluck, Raanan; Shone, Andrew; Andruczyk, Daniel (Physics of plasmas, 2019)
The Hybrid Illinois Device for Research and Applications (HIDRA) is a classical stellarator designed for conducting plasma material interaction experiments and developing novel Plasma Facing Components (PFCs). Notably, the testing of two open-channel liquid lithium PFCs is imminent. Determining the shape of the plasma and its magnetic structure inside HIDRA is essential to carry out these tests. For this, electron traces were captured to build up the images of the HIDRA magnetic flux surfaces for several magnetic configurations, following the same procedure previously employed on the WEGA stellarator coupling an electron gun with a fluorescent detector. The FIELDLINES code has then been used to generate computational surfaces matching the experimental results. The obtained surfaces were found to be subject to a similar n = 1 error field as the one observed on WEGA, suggesting that the origin of this error field is inherent to the HIDRA vacuum vessel. Also, the effect of adding a vertical field was investigated, demonstrating the ability to radially shift the magnetic axis and move to a regime free of low-order rational resonances. This additional control over the HIDRA plasma and magnetic structure allows more freedom in setting up the PFC tests in the limiter and divertor regions.